2012
DOI: 10.1002/smll.201200052
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis‐Free Blue Phase Liquid‐Crystal‐Stabilized by ZnS Nanoparticles

Abstract: Liquid-crystalline blue phases (BPs) have sparked an enormous interest due to their exotic optical properties, exhibiting no birefringence but selective refl ection of circularly polarized light, and potential for advanced applications in a wide variety of fi elds including self-assembling tunable photonic crystals and fast-response display. [ 1 ] BPs are made up of double-twist cylinders arranged in a highly fl uid self-assembled cubic lattice with periods of ∼ 100 nm, which is stabilized by a network of topo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(75 citation statements)
references
References 42 publications
0
75
0
Order By: Relevance
“…It has been experimentally and theoretically confirmed that the BP II and BP I exhibit simple cubic and body-centered cubic nanostructures (Figure 8(a)), respectively. Due to the unique 3D structures of BPLCs, they exhibit many revolutionary features such as optically isotropic and alignment-layer-free, while possess superior electrooptic properties and non-linear optical responses comparable to nematics [134][135][136][137][138][139][140][141][142][143][144][145][146][147][148]. Furthermore, because of the tightly wound spatial arrangement of the crystalline axis, the scattering loss due to thermal fluctuations of the director axis is considerably smaller than nematics, allowing longer interaction length and higher process efficiency.…”
Section: Fibre Arrays Filled With Blue Phase Liquid Crystalsmentioning
confidence: 97%
“…It has been experimentally and theoretically confirmed that the BP II and BP I exhibit simple cubic and body-centered cubic nanostructures (Figure 8(a)), respectively. Due to the unique 3D structures of BPLCs, they exhibit many revolutionary features such as optically isotropic and alignment-layer-free, while possess superior electrooptic properties and non-linear optical responses comparable to nematics [134][135][136][137][138][139][140][141][142][143][144][145][146][147][148]. Furthermore, because of the tightly wound spatial arrangement of the crystalline axis, the scattering loss due to thermal fluctuations of the director axis is considerably smaller than nematics, allowing longer interaction length and higher process efficiency.…”
Section: Fibre Arrays Filled With Blue Phase Liquid Crystalsmentioning
confidence: 97%
“…However, further addition of the NPs amplified the hysteresis loop, which may result from the fact that the cubic structures of BPI would be disordered when doping the excessive amount of the NPs. 4 The V on increases with increasing the concentration of the ZnS NPs ranging from 0.1 wt% to 1.5 wt%, in contrast, the V on would decrease after doping more than 0.5 wt% BaTiO 3 NPs. Importantly, all the samples dispersed by ferroelectric BaTiO 3 NPs show a much lower driving voltage and faster response speed (see ESI †) than that of BPLC doped with ZnS NPs.…”
mentioning
confidence: 93%
“…4 Ferroelectric NPs possess not only a large dipole moment, but also a spontaneous electric polarization which can be reversibly switched by an electric field. The strong local polarization fields from the NPs would polarize a large number of neighboring LC molecules, as shown in Fig.…”
mentioning
confidence: 99%
“…Other techniques for BP stabilisation involve T-shaped molecules, [20] binaphthyl derivatives, [21,22] bent-shaped molecules, [23] hydrogen-bonded selfassembled complexes [24] and nanoparticles. [25][26][27][28][29][30][31] Coles and co-workers reported a dimeric LC having large flexo-electric coefficient and extended the BP range to 44 K. [32] PS-BPLC seems to be most promising but high onstate voltage (V on ), hysteresis, residual transmittance and long-term stability are a few remaining challenges yet to be resolved. The practical applications of BPs are limited due to hysteresis effect and many groups are actively engaged to meet this challenge.…”
Section: Introductionmentioning
confidence: 97%